Relativistic Jet Modeling: Application to AGN - Sauty, C.; Meliani, Z.; Trussoni, E.; Tsinganos, K.; Vlahakis, N. (2006)
AGN are associated with relativistic winds and jets. We discuss the application of meridionally self-similar models to winds and jets from hot relativistic coronae, in particular in the central region of accretion disks. We try to understand the respective role of the disk and the central super massive black hole in the source of the jet as well as the classification of those jets. If the orientation of the jet respectively to the observer is one of the key to understand the standard classification, another parameter is the energy distribution of the magnetic rotator which efficiency should increase between jets from Seyferts and jets from Fanaroff Riley (FR) objects. Moreover the thermal confinement in FRI jets may turn out to be more important than in the magnetically confined FRII jets whose environment is clearly poorer. This scenario deduced from analytical modeling needs further investigation trough numerical simulations.
Keywords: 95.30.Lz; 98.54.Cm; Active and peculiar galaxies and related systems; hydrodynamics